The Electronic Lifestyle In Digital Activities Mediated by the Internet - Gutiérrez Aguilar , Olger; Chicaña Huanca, Sandra (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The study examines how the post-pandemic influenced the digital activities of Peruvian university students, highlighting the rise of an "electronic lifestyle" due to isolation. The relationship between this new style and the value given to the Internet was studied, concluding that this value differs between genders. A survey was carried out on 189 students using a model based on e-lifestyle. The findings reflect new post-pandemic digital needs and interests and a shift in the Internet's perceived significance.